Prevalência de acidentes e complicações em cirurgia oral menor e fatores associados em pacientes da Faculdade de Odontologia da Universidade Federal de Goiás - Sá, Rodrigo Tavares de (2022)
Due to demographic changes, such as population growth and aging, the number of people with untreated oral diseases has increased, with caries and periodontics being the main reasons tooth extraction, leading to dental loss. Among the dental surgical procedures, extractions are a relatively simple procedure that is routinely performed in clinical practice, but is often followed by complications.. The search for these surgical treatments can lead to accidents and post-surgical complications that increase the cost of treatment and negatively impact the quality of life of patients. The objective of this retrospective observational study was to analyze the occurrence of accidents, complications and factors associated with the performance of surgical procedures at the Faculty of Dentistry of the Federal University of Goiás, in addition to verifying the status of dental records filling of this service. A total of 748 medical records of surgical patients were verified for the years 2018 and 2019, while records that belonged to clinics other than the surgical ones, that did not have the patient's name or that were not submitted to a surgical procedure for various reasons were excluded. Thus, data from 698 medical records were tabulated and descriptive and inferential analyzes were performed. The variables analyzed were: type of surgical procedure, number of teeth extracted per patient, presence/absence of intraoperative accidents, postoperative complications (pain, edema, trismus, hemorrhage, infection, paresthesia), use of medication by patients and complementary exams performed. Bivariate analyzes were performed (Mann-Whitney and Chi-Square tests) to study the association between postoperative complications (dependent variable) and sociodemographic (age and sex) and clinical factors (number of extracted teeth and accidents) and between the group of postoperative complications (pain and swelling, pain and trismus, pain and infection, and swelling and trismus).Most of the medical records (93.3%) were properly filled in, with the postal address code (CEP) being the least filled in (36.1%) in the identification field. The analysis of the medical records 88 revealed that in 49.3% of the records, the description of the intraoral examination was not filled out and that the recall of patients for follow-up and/or other procedures was 64.8%. About 46.8% of the patients were not taking medication and the most commonly requested complementary exam was panoramic (52.9%).Females had a higher frequency of attendance (58.2%), and the mean age was 31.14 (SD 13.39). The most performed type of procedure was the extraction of third molars (79.4%, n=554) revealing a mean (1.95; SD 1.429). With regard to accidents, root fractures presented a frequency of 9,74 (n=23), followed by bone board fractures 2,11% (n=5), abrasion of lips and mucous membranes 2,11% (n=5), and fracture of instruments 2,11% (n=5), with the highest frequency in females 52.9%. The most common operative complications were related to pain (11.9%), followed by swelling (7%), which was significantly higher in females (p=0.030), in younger patients (p=0.01) (mean age of 23 years) and who had a greater number of teeth extracted (3 or more). Operative complications were associated with each other, being statistically significant (p ≤ 0.001). The surgical extraction procedure had a low rate of accidents and complications, when compared to literature, despite being performed by undergraduate students. Swelling, as a postoperative complication, was associated with sex, age, and the number of teeth removed. Operative complications were mutually associated.